1988
DOI: 10.1128/aem.54.11.2677-2682.1988
|View full text |Cite
|
Sign up to set email alerts
|

Growth-supporting activity for Legionella pneumophila in tap water cultures and implication of hartmannellid amoebae as growth factors

Abstract: Photosynthetic cyanobacteria, heterotrophic bacteria, free-living amoebae, and ciliated protozoa may support growth of Legionella pneumophila. Studies were done with two tap water cultures (WS1 and WS2) containing L. pneumophila and associated microbiota to characterize growth-supporting activity and assess the relative importance of the microbiota in supporting multiplication of L. pneumophila. The water cultures were incubated in the dark at 35°C. The growth-supporting factor(s) was separated from each cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 26 publications
0
54
0
1
Order By: Relevance
“…Rowbotham (1980) was the first to report the growth of L. pneumophila within Acanthamoeba and Naegleria as a method to enrich for environmental strains of L. pneumophila. Interestingly, others have shown that growth of L. pneumophila in potable water occurs only in the presence of amoebae (Wadowsky et al 1988) and L. pneumophila may remain culturable for up to 6 months in a medium containing Acanthamoeba castellanii (Bouyer et al 2007), whereas free-living Legionella within biofilms may be inactivated within a few weeks (Murga et al 2001;Declerck et al 2007b). Furthermore, active but nonculturable Legionella species have only been propagated or 'resuscitated' culture via co-culture with A. polyphaga and A. castellanii (Hay et al 1995;Steinert et al 1997;Ohno et al 2003;Seno et al 2006;Garcia et al 2007).…”
Section: The Role Of Amoebae In Legionella Pathogenicitymentioning
confidence: 99%
“…Rowbotham (1980) was the first to report the growth of L. pneumophila within Acanthamoeba and Naegleria as a method to enrich for environmental strains of L. pneumophila. Interestingly, others have shown that growth of L. pneumophila in potable water occurs only in the presence of amoebae (Wadowsky et al 1988) and L. pneumophila may remain culturable for up to 6 months in a medium containing Acanthamoeba castellanii (Bouyer et al 2007), whereas free-living Legionella within biofilms may be inactivated within a few weeks (Murga et al 2001;Declerck et al 2007b). Furthermore, active but nonculturable Legionella species have only been propagated or 'resuscitated' culture via co-culture with A. polyphaga and A. castellanii (Hay et al 1995;Steinert et al 1997;Ohno et al 2003;Seno et al 2006;Garcia et al 2007).…”
Section: The Role Of Amoebae In Legionella Pathogenicitymentioning
confidence: 99%
“…Legionella pneumophila is a Gram-negative intracellular pathogen that is the causative agent of Legionnaires' pneumonia (McDade et al, 1977;Burnsed et al, 2007). The major natural reservoir for L. pneumophila is freshwater amoebae (Fields et al, 1984;Wadowsky et al, 1988). The disease in humans is initiated by inhalation of contaminated water sources, and progresses as a result of intracellular replication of L. pneumophila in alveolar macrophages (McDade et al, 1977;Horwitz and Silverstein, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…A central aspect of Legionnaires' disease is the growth of Legionella pneumophila within alveolar macrophages after inhalation of aerosolized fresh water supplies containing L. pneumophila . In culture, growth of L. pneumophila can be observed within monocytes and macrophages (1), as well as within amoebae, the presumed natural reservoir (2)(3)(4). Intracellular replication has been demonstrated to be an essential virulence determinant in animal models (5).…”
Section: Introductionmentioning
confidence: 99%